Pemetaan Mosaic Plot dalam Menganalisis Fundamental Saham Perusahaan pada Aplikasi IPOT IndoPremier Securitas - Ambarsari, Erlin Windia; Sunarmintyastuti, Lies; Lestari, Fibria Anggraini Puji (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
For investors who invest, the selection of issuers is made by considering a company's fundamentals. Several digital securities applications can be used, including Indopremier Sekuritas ipot. However, the analysis is difficult for layman who does not master the basics of finance and business. Therefore, we used a mosaic plot by mapping financial statement data into bar charts. The results showed that the Mosaic plot could present the company's characteristics based on its performance in managing capital from shares so that it can be a reference for investors in considering the selection of issuers based on investment objectives.